Leptin, Adiponectin, and Obesity among Caucasian and Asian Women - Shannon M. Conroy; Weiwen Chai; Unhee Lim; Adrian A. Franke; Robert V. Cooney; Gertraud Maskarinec (Mediators of Inflammation)
Ethnic differences in adipose tissue distribution may contribute to different chronic disease risks across ethnic groups, and adipokines may mediate the risk. In a cross-sectional study, we examined ethnic differences in adipokines and inflammatory markers as related to body mass index (BMI) among 183 premenopausal women with Caucasian and Asian ancestry. General linear models were used to estimate adjusted mean levels of leptin, adiponectin, interleukin-6, and C-reactive protein (CRP). Asian women had significantly lower serum levels of leptin, adiponectin, and CRP than Caucasian participants (P≤.01) across all levels of BMI. Among overweight and obese women, Asians showed a stronger association of CRP with leptin (β=1.34 versus β=0.64) and with adiponectin (β=−0.95 versus β=−0.75) than Caucasians. Compared to Caucasians of similar BMI, Asians may experience a higher chronic disease risk due to lower levels of adiponectin despite their lower levels of leptin.